Recyclable regeneration of NiO/NaF catalyst: Hydrogen evolution via steam reforming of oxygen-containing volatile organic compounds. (15th April 2022) - Ding, Yan; Cai, Yi; Li, Peiwen; Gu, Sasa; Song, Shixing; Guan, Jie; Shen, Yuesong; Han, Yuchen; He, Weiyi
Highlights: NiO/NaF has universality for hydrogen production from OVOCs steam reforming. OVOCs steam reforming over NiO/NaF is a rapid surface reaction process. NaF can promote the efficient adsorption of OVOCs by NiO/NaF. The local electric field generated by F - induces the weakening of the Ni-O bond. Abstract: Regenerable NiO/NaF catalysts break the limitation that catalyst with low specific surface area is difficult to obtain high catalytic activity. In this paper, we investigated the feasibility and universal applicability of hydrogen evolution from different oxygen-containing volatile organic compounds (OVOCs) such as methanol, formaldehyde, formic acid, ethanol, acetic acid, acetone and ethyl acetate steam reforming over NiO/NaF catalysts. The reaction processes and catalytic mechanism of OVOCs steam reforming by 4 wt%NiO/NaF catalyst were analyzed by FESEM, H2 -TPR, in situ DRIFTS, XRD characterization and Density functional theory (DFT) calculation. The results showed that different OVOCs could achieve high-efficiency hydrogen production in steam reforming over 4 wt%NiO/NaF catalyst. The order of conversion easiness was formic acid > formaldehyde > methanol > acetic acid > ethanol > acetone > ethyl acetate. Single-carbon organics such as formic acid, formaldehyde and methanol, had H2 selectivity exceeding 100% at 350, 450 and 500 °C, respectively. The effective reforming temperature rose with the increasing of carbon contents of reactants. Further investigation confirmed that hydrogen production from different OVOCs steam reforming over 4 wt%NiO/NaF catalyst was a rapid surface reaction. And NaF played a key role, which not only promoted the adsorption of the catalyst to the reactants, but also generated local electric field induced by F - ion that weakened the Ni-O bond and reduced the activation energy. As a result, NiO/NaF had better low-temperature redox properties and hydrogen evolution performance than other nickel-based catalysts with big specific surface area.